2022
DOI: 10.3390/antibiotics11050685
|View full text |Cite
|
Sign up to set email alerts
|

Co-Delivery of Nano-Silver and Vancomycin via Silica Nanopollens for Enhanced Antibacterial Functions

Abstract: Infectious diseases caused by bacteria have led to a great threat to public health. With the significant advances in nanotechnology in recent decades, nanomaterials have emerged as a powerful tool to boost antibacterial performance due to either intrinsic bactericidal properties or by enhancing the delivery efficiency of antibiotics for effective pathogen killing. Vancomycin, as one of the most widely employed antimicrobial peptides, has a potent bactericidal activity, but at the same time shows a limited bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This team observed no growth at a concentration of 3.1 µg/mL up to 24 h. In this study, viability was maintained at a concentration of 3 µg/mL, whereas viability was significantly reduced at a concentration of 5 µg/mL [ 22 ]. In a study conducted by Ni et al a 30% decrease in growth was observed after 24 h of S. epidermidis incubation with silver nanoparticles at a concentration of 5 µg/mL and with a particle size of 10–25 nm [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This team observed no growth at a concentration of 3.1 µg/mL up to 24 h. In this study, viability was maintained at a concentration of 3 µg/mL, whereas viability was significantly reduced at a concentration of 5 µg/mL [ 22 ]. In a study conducted by Ni et al a 30% decrease in growth was observed after 24 h of S. epidermidis incubation with silver nanoparticles at a concentration of 5 µg/mL and with a particle size of 10–25 nm [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the efficacy of drugs like vancomycin, gentamicin, and rifampicin, we and others have investigated the use of additives on bone cement to increase the drug release rate or via the use of silver to allow for improved antibacterial effects, allowing the use of lower drug doses [ 8 , 9 , 10 ]. Silver has been shown to have additive effects with vancomycin [ 11 , 12 , 13 ] and rifampicin [ 14 , 15 ] and includes the benefit of expanding the spectrum of bacterial killing to Gram-negative bacteria [ 11 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Ag nanoparticles’ antibacterial properties are related to their ability to attach to cell membranes and then their release into bacterial cells, both of that contribute to their high level of activity. Due to their increased surface energy, Ag nanoparticles, on the other hand, are extremely quickly oxidized and aggregated, limiting their antibacterial efficacy in clinical settings 15 , 16 . To address these challenges, several Ag-carried substances, such as zeolite, carbon, silica, and titanium dioxide, have been created to enhance effectual as well as multipurpose functions in the areas of infection prevention and control, tissue regeneration, wound healing, and the treatment of oral disease 16 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that there are several techniques to synthesize nanostructures 16 , 27 30 , their environmentally friendly green synthesis has gained attention over recent years 27 , 31 . When it comes to reductants, green synthesis or novel synthesis methods can make use of a wide range of resources such as plant extracts, microorganisms, biomass, and many other types of chemicals 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%